The Asymptotes of Power - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2012)
FROM THE CLOSING COMMENTS BY JONATHAN NITZAN: Today's talk has, like the one I gave at last year's conference on Capital as Power, presented my joint work with Bichler on the present crisis. Last year, I argued that this crisis is a systemic one, and that capitalists were struck by systemic fear – a primordial consternation for the very existence of their system. My purpose today has been to explain why. In order to do so, I have set aside the liberal-democratic façade that economists label 'the economy' and instead concentrated on the nested hierarchies of organized power. The nominal quantity of capital, I've argued, represents not material consumption and production, but commodified power. In modern capitalism, the quantities of capitalist power are expressed distributionally, as differential ratios of nominal dollar magnitudes. And the key to understanding capital as power is to decipher the connection between the qualitative processes of power on the one hand, and the nominal distributional quantities that these processes engender on the other. I have dissected, step by step, the national income accounts of the United States, from the most general categories down to the net profits of the country's largest corporations. I have shown that, from the viewpoint of the leading corporations, most of the redistributional processes – from the aggregate to the disaggregate – are close to being exhausted. By the end of the twentieth century, the largest U.S. corporations, approximated by the top 0.01%, have reached an unprecedented situation: their net profit share of national income hovers around record highs, and it seems that this share cannot be increased much further under the current political-economic regime. This asymptotic situation, Bichler and I believe, explains why leading capitalists have been struck by systemic fear. Peering into the future, they realize that the only way to further increase their distributional power is to apply an even greater dose of violence. Yet, given the high level of force already being exerted, and given that the exertion of even greater force may bring about heightened resistance, capitalists are increasingly fearful of the backlash they are about to unleash. The closer they get to the asymptote, the bleaker the future they see. It is of course true that no one knows exactly where the asymptote lies, at least not before the ramifications of approaching it become apparent. But the fact that, over the past decade, capitalists have been pricing down their assets while their profit share of income hovers around record highs suggests that, in their minds, the asymptote is nigh.
Keywords: 330; capitalization; distribution; power; systemic crisis; United States